Cost-Benefit Analysis of Cannabis Legalization in the Czech Republic - Jirsa, Pavel; Sáenz de Viteri Vázquez, Andrea; Cingl, Lubomír, 1984-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
In the Czech Republic, there is growing political discussion on the regulation of the cannabis market and legalization of possession and self-growing of cannabis. This thesis examines the potential economic, social, and public health impacts of cannabis legalization in the Czech Republic through a comprehensive cost-benefit analysis. By evaluating data from countries with existing legalization frameworks and considering the socio-economic context of the Czech Republic and proposed regulation framework, the study explores potential fiscal benefits, such as tax revenue and reduced law enforcement costs, against possible social costs, including public health implications and regulatory challenges. The research aims to provide evidence-based insights into how legalization could affect key stakeholders, such as the government and society at large. The findings seek to inform policymakers about the potential market development and trade-offs and opportunities associated with the legal regulation of cannabis. The results show significant positive impact of the proposed regulation framework both on the state budget and in terms of the net socioeconomic benefits for the Czech Republic and its residents.
Vedoucí práce: Andrea Sáenz de Viteri Vázquez
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses